Restauração autonômica cardíaca pós exercício físico em indivíduos com diferentes índices de massa corporal - Miranda, Rômulo Mariano de (2021)
High-intensity interval physical exercise has been widely prescribed on the basis of less time spent to improve body composition. Thus, individuals with excess body mass, especially young people, have performed this form of exercise. High-intensity physical exercises cause major adjustments in cardiac autonomic control, which may delay cardiac autonomic restoration in the subsequent period. Individuals with obesity may have their cardiac autonomic control altered, however, it is not known whether these individuals may present complete vagal reactivation later than their eutrophic peers. Objective: To verify whether overweight/obesity influences complete vagal reactivation after high-intensity interval exercise in young adults. Method: 36 men aged between 18 and 25 years, body mass index between 18,6 – 39,9 participated in the study kg/m2, untrained, divided into Eutrophic and Overweight/Obese groups. The study consisted of a High Intensity Interval Exercise session (EIAI: 20 min at 80-90% of FCR). Cardiac autonomic control was analyzed by measuring heart rate variability (HRV) and obtaining HRV indices in the time domain (RMSSD and SDNN) and frequency (LF, HF, LF:HF). HRV was measured during rest, exercise, and subsequent recovery for 120 minutes. Results: HRV indices were similar between groups at rest and during post-exercise recovery. Based on the RMSSD index, the time to complete cardiac vagal reactivation post-exercise did not differ between the eutrophic and overweight/obese groups (48 ± 25.52 vs. 60 ± 17.32 min). Conclusion: Overweight/obesity did not influence cardiac autonomic restoration after high-intensity interval exercise.